A novel FBN2 mutation in a Chinese family with congenital contractural arachnodactyly. Issue 1 (5th March 2015) - Liu, Wei; Zhao, Ning; Li, Xue-fu; Wang, Hong; Sui, Yu; Lu, Yong-ping; Feng, Wen-hua; Ma, Chao; Han, Wei-tian; Jiang, Miao
Abstract : Congenital contractural arachnodactyly (CCA, OMIM:121050) is an autosomal dominant condition that shares skeletal features with Marfan syndrome (MFS, OMIM:154700), including contractures, arachnodactyly, dolichostenomelia, scoliosis, crumpled ears and pectus deformities but excluding the ocular and cardiovascular complications that characterize MFS. These two similar syndromes result from mutations in two genes belonging to the fibrillin family, FBN1 and FBN2, respectively. We successfully identified a novel FBN2 mutation (C1406R) in a Chinese family with CCA for over five generations. This mutation was detected in the patients of this family but not in the seven unaffected family members or 100 normal individuals. SIFT and PolyPhen analyses suggested that the mutation was pathogenic. We identified a missense mutation in the calcium binding‐epidermal growth factor (cbEGF)‐like domain. Our study extends the mutation spectrum of CCA and confirms a relationship between mutations in the FBN2 gene and the clinical findings of CCA. Abstract : We identified a novel FBN2 mutation (C1406R) in a Chinese family with CCA. The mutation presented in the patients of this family but not in unaffected members. SIFT and PolyPhen analyses suggested that the mutation was pathogenic. The mutation was located in the calcium‐binding epidermal growth factor‐like domain.